AGE AND GROWTH OF 'GHOL', PSEUDOSCIAENA DIACANTHUS (LACEPEDE) IN BOMBAY AND SAURASHTRA WATERS - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
IN an earlier paper the present author (Rao, 1961) had shown that the scalesand otoliths of 'Ghol', Pseudosciaena diacanthus (Lacepede), a commerciallyimportant sciaenid in Bombay and Saurashtra waters, are useful as ageindicators of this species. The results of studies on the growth of this fishbased on these structures and the length frequency data for the period1958-62 are presented here. Further, von Bertalanffy growth equationwas fitted to the length-at-age data and estimates of the parameters wereobtained and compared with similar estimates of other sciaenids fromdifferent regions.